DINAMIKA KONFLIK KERUSUHAN MEI 1998 DI KOTA SURAKARTA MELALUI PERSPEKTIF KORBAN - Lydiana Salim; Akhmad Ramdhon (Universitas Sebelas Maret (UNS), 2020)
The May 1998 riots that occurred were the result of a collection of political, social and economic events that occurred during the New Order. Events of the May 1998 riots in the city of Surakarta had a great influence on the lives of the victims. In the aftermath of the May 1998 riots, several victims were declared traumatized to the extent of damaging their homes and businesses. The purpose of this study was to determine the chronology of the May 1998 riots and analyze the dynamics of the May 1998 riots in the city of Surakarta. The theory in this research is the Conflict theory from Ralf Dahrendorf. This type of research is a qualitative research with an ethnographic approach in the city of Surakarta. The sampling technique with snowball sampling technique. The research informants consisted of student activists and formal organizations, journalists, religious leaders and victims of the May 1998 incident. Data were collected by observation, in-depth interviews and documentation. To test data validity with source triangulation. The data analysis technique uses an interactive analysis model from Miles and Huberman. The results showed that the May 1998 riots which occurred for two days caused damage and material losses. Mass amok movements occur regularly by doing damage, looting to arson in every corner of the city. After the May 1998 riots, the city's economic sector did not work. Some entrepreneurs were forced to stop production for a while due to the damage they experienced. Post-disaster economic reconstruction is carried out by the government and community groups by providing assistance to victims. From social conditions, after the May 1998 riots some victims decided to flee to areas that were safe from conflict. After the riots of May 1998 victims were pressured by the community in the form of negative stigma. Discomfort and fear experienced by the people after the riots began to be addressed by involving religious institutions. Religious institutions work together in creating communication forums between communities. in terms of the psychological condition of the people after the riots, some victims experienced trauma from witnessing firsthand the atrocities that occurred.